2007
DOI: 10.1108/00907320710774346
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance research on the free web: a selected annotated guide

Abstract: Purpose -The web offers a large and ever expanding range of information sources on the popular and widely researched topic of corporate governance. This paper aims to introduce keys sites of quality and relevance to those interested in researching the field of corporate governance using freely available web resources. It will also aims to prove useful to librarians who wish to develop web-based subject pathfinders in this field or who want simply to connect with and build their knowledge of major topics and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Moreover, many of the normative assumptions surrounding not-for-profits (especially around charitable status) are unfounded since not-for-profits are very variable and some may operate in very competitive markets (Maitlis 2004). Indeed, some commentators note a convergence between governance in the for-and not-for-profit sectors as the 'new public management' has encouraged moves towards the adoption of organisational structures that mimic the commercial sector (Ashburner et al 1996;Peck et al 2004;Freeman and Peck 2007;Tacon and Walters 2016); conversely, for-profit organisations are now required to be heedful of their 'corporate and social responsibilities' in the pursuit of 'sustainable' governance (Huse 2005), which acknowledges wider obligations towards non-shareholder stakeholders (Bury and Leblanc 2007).…”
Section: Defining the Scope Of The Researchmentioning
confidence: 99%
“…Moreover, many of the normative assumptions surrounding not-for-profits (especially around charitable status) are unfounded since not-for-profits are very variable and some may operate in very competitive markets (Maitlis 2004). Indeed, some commentators note a convergence between governance in the for-and not-for-profit sectors as the 'new public management' has encouraged moves towards the adoption of organisational structures that mimic the commercial sector (Ashburner et al 1996;Peck et al 2004;Freeman and Peck 2007;Tacon and Walters 2016); conversely, for-profit organisations are now required to be heedful of their 'corporate and social responsibilities' in the pursuit of 'sustainable' governance (Huse 2005), which acknowledges wider obligations towards non-shareholder stakeholders (Bury and Leblanc 2007).…”
Section: Defining the Scope Of The Researchmentioning
confidence: 99%
“…Harris (1989) discovered that boards were, in fact, quite removed from infl uential actions and decisions. Katsioloudes and Tymon (2003) noted evidence of a perceived lack of participation in strategic planning by boards populated by volunteers, and Bury and Leblanc's (2007) research has suggested that there is no direct relationship between board structure and corporate performance. While there is a substantial body of knowledge about strategy and the strategic management of organisations (Chandler, 1962;Mintzberg, 1987;Mintzberg, Ahlstrand & Lampel, 1998;Porter, 1985), there are recognised gaps in our understanding of board involvement in strategy (Johnson, Daily, & Ellstrand, 1996;Ruigrok et al, 2006;Schmidt & Brauer, 2006;Stiles, 2001;van der Walt & Ingley, 2003).…”
Section: Governance Practicementioning
confidence: 99%
“…Notably, the research has alluded to board composition (Carter, Simkins, & Simkins, 2003;Rutherford & Buchholtz, 2007), board leadership (Daily, McDougall, Covin, & Dalton, 2002;Dalton, Daily, Ellstrand, & Johnson, 1998), the relationship between the board and CEO (Hoye, 2002;Rechner & Dalton, 2006), and the infl uence of culture and processes (Gray, 2007;Minichilli, Gabrielson, & Huse, 2007). It appears, however, that greater attention is required to enhance one of the primary roles of boards, that of strategic capability, with the ultimate intention of The current case study takes place against a backdrop of governance theory and discussion which has largely developed over the last 65 years with corporate governance developing into a robust and information-rich fi eld of interest (Bury & Leblanc, 2007). Although initially with a predominant leaning toward the private sector, increasingly, attention is also being directed to non-profi t organisations.…”
Section: Introductionmentioning
confidence: 99%